Mathematics

Question

Simplify a - {5b - [a - (3b - 2c) + c - (a - 2b - c)]}.

2 Answer

  • a - {5b - [a - (3b - 2c) + c - (a - 2b - c)]}.

    =a - {5b - [a - 3b + 2c + c - a + 2b + c]}

    =a - {5b - a + 3b - 2c - c + a - 2b - c}

    =a - 5b + a - 3b + 2c + c - a + 2b + c

    =a - 6b + 4c

  • The answer is a - 6b + 4c.

    The given equation is  a - {5b - [a - (3b - 2c) + c - (a - 2b - c)]}.

    To simplify the  given equation.

    What is simplification?

    The process of making something simpler or easier to do or understand.

    a - {5b - [a - (3b - 2c) + c - (a - 2b - c)]}.

    =a - {5b - [a - 3b + 2c + c - a + 2b + c]}

    =a - {5b - a + 3b - 2c - c + a - 2b - c}

    =a - 5b + a - 3b + 2c + c - a + 2b + c

    =a - 6b + 4c

    So, the answer is a - 6b + 4c.

    Learn more about  simplification here:

    https://brainly.com/question/2774263

    #SPJ5

NEWS TODAY